Sustainable Thematic Village: Strengthening Al-Quran Literacy Through the Yanbu'ul Qur'an Method in Increasing Al-Qur'an Reading for the Community in Lancar Village, Pamekasan - Fauzan; Agung Saputra; Affanil Yoga H; Ayatullah Ali H; Iwan Ghufroni; M. Silvan Qoriy (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
This study aims to explore the enhancement of Qur'anic literacy through the Yanbu'ul Qur'an method to improve the ability to read the Qur'an among the community of Lancar Larangan Village, Pamekasan. Qur'anic literacy is an important aspect of religious education that can strengthen the understanding and practice of Islamic teachings. The Yanbu'ul Qur'an method, which focuses on interactive and contextual approaches, is expected to address the challenges faced by the community in reading the Qur'an correctly. This research employs a qualitative method with a case study approach, involving active participation from the local community. The results indicate that the implementation of this method successfully improved the skills of reading the Qur'an, deepened the community's understanding of its content, and strengthened their commitment to practicing religious teachings. These findings are expected to serve as a reference for the development of Qur'anic literacy programs in other areas and to support efforts to enhance the quality of religious education in Lancar Larangan Village, Larangan District, Pamekasan Regency.